Quercus chapmanii, Chapman Oak - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana (EDIS)
FOR 243, a 2-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, and Heather V. Quintana, describes this native oak, naturally found in the dry, xeric habitats of sandy ridges and coastal dunes throughout most of Florida and coastal Alabama, Georgia, and the southern portion of South Carolina — scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, May 2010.